EFFECTIVENESS OF STANDARDIZED PATIENTS AND ROLE-PLAY SIMULATION METHODS IN IMPROVING SELF-CONFIDENCE AND THERAPEUTIC COMMUNICATION SKILLS OF NURSING STUDENTS - Bagus Dwi Cahyono; Ida Zuhroidah; Mokhammad Sujarwadi (Nurse and Health: Jurnal Keperawatan, 2020)
Background: Communication skills are critical skills that must be possessed by nurses because communication is a dynamic process that is used to collect assessment data, provide education or health information to influence clients to apply it in life, show caring, provide comfort, foster self-confidence and, value respect - client value. Nurses in communicating with clients must have high confidence in the effect of these communications.Objectives: The purpose of this study was to analyze the differences in the effect of standardized patient simulation methods and role play in increasing self-confidence and therapeutic communication skills of students of the Nursing Academy of Pasuruan.Methods: The design of this study is the quasi experimental study. There are two therapeutic communication training groups. Group A uses a Standardized Patient (SP) and, Group B uses the role play (RP) method. The population in this study were students of the Nursing Academy of Pasuruan, and the sample was taken by simple random sampling with a sample size group of 16 standardized patients and a roleplay group of 16 people. The measuring instrument used was an observation sheet on therapeutic communication skills and a questionnaire on confidence in therapeutic communication. The effectiveness of the two methods was analyzed by the non-parametric test, namely the Mann Whitney test, to test 2 unpaired samples.Results: The results of this study indicate that there are differences in standardized patient methods and role play on self-confidence and therapeutic communication skills in nursing academy students who are statistically significant at 0.03 (p=0.05).Conclusion: The standardized patient method is more effective in increasing self-confidence and therapeutic communication skills in nursing academy students compared to the roleplay method. Keywords: Standardized Patient, Roleplay, Therapeutic Communication, Self-Confidence